Influencing factors of cancer prevention and control among urban and rural adults in Fujian, China: A cross-sectional survey - Yang, Tian Bao; Lin, Xiu Jing; Lin, Jia Ling; Chen, Wei-Ti; Huang, Fei Fei (Frontiers in Public Health, 2022)
Objective: Cancer burden can be reduced when the population’s knowledge of cancer prevention and control measures is increased. However, current epidemiological research investigating cancer prevention and control knowledge in China is limited. This study aimed to examine the core knowledge levels of cancer prevention and control measures as well as its influencing factors among adults in Fujian, China. Study design: A cross-sectional study. Methods: From September to December 2021, a total of 2,440 Chinese urban and rural adults from Fujian Province, located in Southeastern China, were randomly selected for this cross-sectional study. The probability proportionate approach to sampling was used. A 38-item questionnaire that covered demographics and basic knowledge of cancer, including concepts, screening, therapy, and rehabilitation-related key points was used to measure knowledge levels of cancer prevention and control measures among 2,074 participants. The level of each participants’ core knowledge of cancer prevention and control measures was defined as a rate calculated by the number of correct answers divided by the total number of questions. The binary logistic regression model was used to determine if influencing factors were associated with core knowledge awareness. Results: In total, 1,290 participants (62.2%) were in the low knowledge group and 784 (37.8%) were in the high knowledge group. The average knowledge rate of cancer prevention and control measures among all participants was 56.01%. Participants from urban areas, who held white-collar jobs, were married, had a bachelor’s degree or above, had a family history of cancer, or self-rated their health level as good or average were associated with higher rates of cancer prevention and control core knowledge (overall p<0.05). Conclusions: These findings may assist healthcare providers and/or researchers in designing effective primary preventive interventions to enhance the general population’s cancer prevention and control knowledge, and subsequently decrease the cancer burden in China.